Mold Filling Simulation For Injection Molding Of Natural Rubber Compound In Glove Fabrication - Maturidi, Nurul Ain Abu Mansor (Universiti Sains Malaysia, 2017)
Rubber injection molding is a process whereby a rubber mix is injected into a closed mold where the material is shaped to the desired geometry. The aim of the study was to observe and understand the behavior of the mold filling of natural rubber compound in injection molding. The numerical studies on mold filling of glove fabrication in injection molding were carried out. Injection moldings with natural rubber compounds having sections with thickness of 0.4, 0.5 and 0.6 mm have been prepared. CADMOULD software was used in the simulation with the Cross viscosity model. The effects of variation in process parameters such as temperature, location of gate, and viscosity on its mold filling were studied. A CADMOULD is employed to investigate appropriate rubber behavior during curing and viscosity model, respectively. Vulcanization at different quantities of gate have advantages in curing thin sections adjacent to thick ones because of their superior reversion resistance. Increase in temperature resulted in higher flow rate due to increase in viscosity. Cure time is highly dependent on injection temperature and the art of injection molding is to inject at the highest possible temperature consistent with freedom from scorch. The injection temperature of natural rubber depends on the injection molding machine variables such as barrel temperature. The simulation results are in good conformity and the strength of CADMOULD Rubber in handling mold filling in glove fabrication problems is proved to be excellent.